2021
DOI: 10.1111/tbed.14014
|View full text |Cite
|
Sign up to set email alerts
|

Detection of newly introduced Y280‐lineage H9N2 avian influenza viruses in live bird markets in Korea

Abstract: We report the first detection of Y280‐lineage H9N2 avian influenza viruses in live bird markets in Korea during July 2020. The viruses were isolated from domestic ducks and chickens traded in three markets in two different provinces, indicating dispersal of the newly introduced viruses. Complete genome sequencing and comparative phylogenetic analyses of all eight gene segments of the viruses showed high nucleotide homology to a Y280‐lineage H9N2 avian influenza virus isolated in a chicken farm in China, which … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 11 publications
(18 reference statements)
1
8
0
Order By: Relevance
“…These findings suggest that the isolates may have the potential ability to infect mammalian species, including humans, demonstrating a possible public health risk. Overall, the genetic analysis results from this study coincide with a recent study indicating that Y280-like strains circulating in Korean LBMs are likely direct descendants of the A/chicken/Shandong/1844/2019 strain, without further reassortments with any other influenza viruses (Youk et al, 2021). Virus-neutralizing antibodies to the new Y280-like H9N2 virus were detected in field serum samples collected from affected chicken farms.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…These findings suggest that the isolates may have the potential ability to infect mammalian species, including humans, demonstrating a possible public health risk. Overall, the genetic analysis results from this study coincide with a recent study indicating that Y280-like strains circulating in Korean LBMs are likely direct descendants of the A/chicken/Shandong/1844/2019 strain, without further reassortments with any other influenza viruses (Youk et al, 2021). Virus-neutralizing antibodies to the new Y280-like H9N2 virus were detected in field serum samples collected from affected chicken farms.…”
Section: Discussionsupporting
confidence: 87%
“…Even the incidence of these strains fell sharply over time after introducing inactivated H9N2 vaccines, in conjunction with strengthened control measures to prevent HPAI (Choi et al, 2008;Mo et al, 2016). It was not until recently that surveillance programmes identified that the non-indigenous H9N2 strains from the Y280-like lineage circulated in Korean LBMs (Heo et al, 2021, Youk et al, 2021. These LBM Y280-like strains would likely have spilled over into Korean industrial poultry populations, causing field infections nationwide.…”
Section: Discussionmentioning
confidence: 99%
“…Outbreaks of the Y439 lineage of H9N2 AI decreased after vaccinating layer and broiler breeders since 2007. However, even after vaccination, the virus has continued to circulate mainly in Korean native chicken farms and live bird markets (LBM), there have been no reports since it was last detected in 2018 [ 8 9 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, it was reported in Japan and eastern Russia, which does not border China [ 19 20 ]. In addition, the Y280 lineage of H9N2 AIV was first isolated from LBMs in South Korea in June 2020 and has spread rapidly nationwide [ 9 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Large-scale vaccination with commercially available monovalent or mixed H9N2 inactivated vaccines contributes substantially to the control of H9N2 outbreaks (6). However, endemic H9N2 avian influenza, especially those caused by the G57 genotype of the virus, has not been effectively controlled (23)(24)(25)(26). In addition, there is no available avian H3N2 vaccine.…”
Section: Introductionmentioning
confidence: 99%